Mechanism‐driven strategies for prevention of rheumatoid arthritis. Issue 3 (15th June 2022) - Holers, V. Michael; Kuhn, Kristine A.; Demoruelle, M. Kristen; Norris, Jill M.; Firestein, Gary S.; James, Eddie A.; Robinson, William H.; Buckner, Jane H.; Deane, Kevin D.
Abstract: In seropositive rheumatoid arthritis (RA), the onset of clinically apparent inflammatory arthritis (IA) is typically preceded by a prolonged period of autoimmunity manifest by the presence of circulating autoantibodies that can include antibodies to citrullinated protein antigens (ACPA) and rheumatoid factor. This period before clinical IA can be designated preclinical RA in those individuals who have progressed to a clinical diagnosis of RA, and an "at‐risk" status in those who have not developed IA but exhibit predictive biomarkers of future clinical RA. With the goal of developing RA prevention strategies, studies have characterized immune phenotypes of preclinical RA/at‐risk states. From these studies, a model has emerged wherein mucosal inflammation and dysbiosis may lead first to local autoantibody production, which should normally be transient, but instead is followed by a systemic spread of the autoimmunity as manifested by serum autoantibody elevations, ultimately driving the development of clinically identified joint inflammation. This model can be envisioned as the progression of disease development through serial "checkpoints" that in principle should constrain or resolve autoimmunity; however, instead, the checkpoints "fail" and clinical RA develops. Herein we review the immune processes that are likely to be present at each step and the potential therapeutic strategies that could be envisioned to delay, diminish, halt, or even reverse the progression to clinical RA. Notably, these prevention strategies could utilize existing therapies approved for clinical RA, therapies approved for other diseases that target relevant pathways in the preclinical/at‐risk state, or approaches that target novel pathways. Abstract : Strategies for rheumatoid arthritis (RA) prevention should move away from a strict focus on the use of therapies that have been approved based on effects on "synovial" disease toward a more mechanism‐based approach targeting stage‐specific "checkpoint" mechanisms of disease development. Key points: Significant findings of the study: Seropositive rheumatoid arthritis (RA) evolves over years before the development of clinically apparent inflammatory arthritis. Emerging data support a model wherein mucosal inflammation precedes the development of systemic autoimmunity, followed by the development of synovitis. The development of RA may entail multiple "endotypes" across individuals who ultimately develop clinical disease. What this study adds: Mechanisms that should normally constrain RA‐related autoimmunity at specific checkpoints, including mucosal and systemic processes that limit autoimmunity, appear to fail during the preclinical development of RA. By understanding and targeting these failed mechanisms, it may be possible to prevent, or minimally ameliorate, the development of classified RA.